Ethics Beyond Being?: Human Dignity and the Ontology of the Good in Twentieth-Century Catholic Thought - Michael Dominic Taylor (Religions)
The terrors of the twentieth century left those who still believed in man’s capacity for the Good seeking new approaches. Martin Heidegger’s anti-metaphysical critique had called into question the systems of the past. In Poland, where these crises were felt acutely by a profoundly Catholic society, two thinkers can serve as a case study that helps give insight into the rebuilding of an ethical society and system of thought from within, namely, Jozef Tischner and Karol Wojtyła (John Paul II). Regarding the crucial question of human dignity, Tischner follows Emmanuel Levinas, who seems to have accepted Martin Heidegger’s anti-metaphysical critique, to a conception of goodness “beyond being” by which being becomes the enemy of goodness. This position is contrasted with that of John Paul II and others—such as Hans Urs von Balthasar, Robert Spaemann, and D. C. Schindler—who adhere to the comprehension of being and goodness as coextensive and bring it into the twenty-first century. While numerous points of contact exist, the contrast between Tischner and John Paul II is one of alternate priorities—phenomenology or metaphysics, respectively—which results in two different trajectories for comprehending ethics, encounter, solidarity, and the Good. While Tischner’s openness to dialogue with his contemporary world is laudable and necessary, John Paul II’s insistence on the ontological grounding of the Good is indispensable.